Reviews of recent publications (Studies in 20th & 21st Century Literature, 2001)
Alonso, Carlos J. The Burden of Modernity: The Rhetoric of Cultural Discourse in Spanish America Reviewed by Melvin S. Arrington, Jr. Kolocotroni, Vassiliki, Jane Goldman, and Olga Taxidou, eds, Modernism: An Anthology of Sources and Documents Reviewed by Gerd Bayer Motte, Warren. Small Worlds: Minimalism in Contemporary French Literature Reviewed by William Cloonan Melton, Judith M. The Face of Exile: Autobiographical Journeys Reviewed by Claude P. Desmarais Redding, Arthur. Raids on Human Consciousness: Writing, Anarchism, and Violence Reviewed by Gail Finney Chambers, Ross. Facing It: AIDS Diaries and the Death of the Author Reviewed by Melissa A. Fitch Marx-Scouras, Danielle. The Cultural Politics of Tel Quel: Literature and the Left in the Wake of Engagement Reviewed by Diane Fourny Foster, David William. Buenos Aires: Perspectives on the City and Cultural Production Reviewed by Gustavo Geirola Nelson, Ardis L., ed. Guillermo Cabrera Infante: Assays, essays, and other arts Reviewed by José Luis Martinez-Dueñas Fox, Claire F. The Fence and the River: Culture and Politics at the U.S.-Mexico Border Reviewed by Robert Neustadt
Keywords: Carlos J. Alonso; The Burden of Modernity: The Rhetoric of Cultural Discourse in Spanish America; Melvin S. Arrington Jr.; Vassiliki Kolocotroni; Jane Goldman; Olga Taxidou; Modernism: An Anthology of Sources and Documents; Gerd Bayer; Warren Motte; Small Worlds: Minimalism in Contemporary French Literature; William Cloonan; Judith M. Melton; The Face of Exile: Autobiographical Journeys; Claude P. Desmarais; Arthur Redding; Raids on Human Consciousness: Writing Anarchism and Violence; Gail Finney; Ross Chambers; Facing It: AIDS Diaries and the Death of the Author; Melissa A. Fitch; Danielle Marx-Scouras; The Cultural Politics of Tel Quel: Literature and the Left in the Wake of Engagement; Diane Fourny; David William Foster; Buenos Aires: Perspectives on the City and Cultural Production; Gustavo Geirola; Ardis L. Nelson; Guillermo Cabrera Infante: Assays essays and other arts; José Luis Martinez-Dueñas; Claire F. Fox; The Fence and the River: Culture and Politics at the U.S.-Mexico Border; Robert Neustadt